PERTARUNGAN KONSTITUSIONAL PADA PEMILU 2014 DAN KONSOLIDASI HAK-HAK PEMILIH DI INDONESIA - Jacoba Sahalessy (Faculty of Law, Universitas Pattimura, 2015)
Election is an important pillar of the concept of rule of law and the concept of democracy. Election is a constitutional fight for their regime's power. The shift mechanism is expected by the constitution serves as a form of accountability and control. Election is a strategic moment in which the right of voters not only show concern, but also determine the path direction of the country the next 5 years in a political system based on the law. The important role played by the voters will be consolidated agenda of change to be achieved in the life of the country.